Faktor Pemutusan Kontrak pada Proyek Konstruksi Berbasis E-Tendering di Kota Surabaya - Putra, Fanji Indrajaya; Beatrix, Michella; Firmansyah, Mochamad (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
Contract termination in construction projects is a critical issue that can significantly affect project time and cost performance. This study aims to identify the dominant factors causing contract termination and analyze their impact on construction project performance in e-tendering-based projects in Surabaya. A quantitative approach was applied using questionnaire data collected from 46 respondents, including contractors, consultants, and project personnel. Data were analyzed using descriptive statistics and simple linear regression. The results indicate that delay in work progress is the most dominant factor, and contract termination has a strong influence on project time and cost, with a correlation value of 0.881. Therefore, improving project control and enhancing human resource competence are essential to minimize the risk of contract termination.